MODERN CHALLENGES AND DEVELOPMENT TRENDS IN THE ACTIVITIES OF EXECUTIVE AUTHORITIES - Behzodbek Bahromjon o‘g‘li, Ibrohimov (Antis Publisher, 2025)
Objective: This study critically analyzes the structural, legal, and operational challenges faced by executive authorities in Uzbekistan, aiming to propose mechanisms for enhancing efficiency and public trust through reforms. Method: A qualitative approach is employed, focusing on a review of recent presidential decrees, government programs, and key performance indicators (KPIs), with an emphasis on the implications of digital platforms and interagency cooperation. Results: The findings indicate that although reforms such as the introduction of KPIs and digital services have improved service delivery, persistent issues, including centralized decision-making, unclear functional divisions, and inadequate interagency coordination, continue to impede effectiveness. Novelty: This article contributes original insights by linking administrative performance with governance innovation, utilizing recently enacted legislation and governmental initiatives as empirical anchors. The study emphasizes the need for continued institutional reforms, legal clarification of competencies, digitalization, and empowerment of local authorities to foster citizen-centric governance and improve public administration in Uzbekistan.